STRATEGI MAHASISWA UNTUK MENGHILANGKAN RASA CEMAS KETIKA BERBICARA BAHASA INGGRIS DI KELAS - Asrida, Deni (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
Speaking anxieties become a big problem for the students in learning english nowadays. This paper discusses about students strategies in overcoming speaking anxieties in front of the class and its causing factors. Based on the finding, it is found that there are some factors caused students speaking anxietiesin the class namely students were afraid in making mistakes, they have little confidence in speaking english, they often lose their ideas when speaking in front of the class, they also afraid speaking spontaneously in the class. Meanwhile, it is also found that the students applied some strategies in overcoming speaking anxieties in the class namely the students try to be rilexs during speaking class, make a notes, consider there is no audience seeing his/her performance, practice in front of the mirrorr, practice with their classmate.